Benefiicial effects of a novel polyherbal formulation on the skeletal muscle antioxidant status, infllammation, and muscle-signaling proteins in exercised rats - Tuzcu, Mehmet; Ozdemir, Oguzhan; Orhan, Cemal; Şahin, Nurhan; Morde, Abhijeet; Padigaru, Muralidhara; Şahin, Kazım (Tubitak Scientific & Technological Research Council Turkey, 2024)
Background/aim: Exhausting exercise can damage muscle tissue due to free radical interactions. It is hypothesized that the increase in free radicals following muscle injury, either due to oxidative damage to biomolecules or the activation of inflammatory cytokines, may lead to secondary muscle damage. This study investigated the effects of a novel joint health formula (JHF) containing bisdemethoxycurcuminenriched curcumin, 3-O-Acetyl-11-keto-beta-boswellic acid-enriched Boswellia (AKBA), and Ashwagandha on exhaustion time, grip strength, antioxidant status, and muscle-signaling proteins in exhaustively exercised rats. Materials and methods: Twenty-eight rats were divided into four groups :Control(C), exercise(E),E+JHF100(100mg/kg),andE+JHF200(200mg/kg). Results: An increase in time to exhaustion and grip strength was recorded with JHF supplementation in a dose-dependent manner (p < 0.0001). In addition, serum and muscle lactate dehydrogenase, malondialdehyde, myoglobin, creatine kinase, and lactic acid concentrations were decreased in the groups supplemented with JHF, particularly at the high dose of JHF (200 mg/kg) (p < 0.0001 for all). JHF supplementation also increased antioxidant enzyme activities and suppressed the production of inflammatory cytokines compared to the exercise group (p < 0.0001). Moreover, JHF reduced the levels of PGC-1 alpha, p-70S6K1, MAFbx, MuRF1, and p-mTOR proteins in muscle tissue compared to the exercise group (p < 0.05), being more effective at high doses. Conclusion: These findings show that JHF might reduce muscle damage by modulating ant iinflammatory, antioxidant, and muscle mass in exhausted rats. At the same exercise and
Keywords: Joint health formula; inflammation; exhaustion; exercise; antioxidant